Susceptibility to Ingroup Influence in Adolescents With Intellectual Disability: A Minimal Group Experiment on Social Judgment Making - Egger, Sara (Frontiers in Psychology, 2021)
Adolescents with intellectual disability (ID) experience challenges and uncertainty when making judgments about other people’s intentions. In an attempt to achieve certainty, they might exhibit judgment tendencies that differ from those of typically developing adolescents. This study investigated social judgment making in adolescents with ID (n=34, Mage=14.89 years, SD=1.41 years) compared with chronological age-matched adolescents without ID (n=34, Mage=14.68 years, SD=1.15 years) and mental age-matched children (n=34, Mage=7.93 years, SD=.64 years). Participants used a computer-based task to judge the hostility of persons (fictitious characters). Adolescents with ID were found to make more polarizing judgments (i.e., either positive or negative, as opposed to moderate judgments) and were more likely to be guided by the opinions of a fictitious peer ingroup (minimal group) compared with adolescents without ID. No such differences were found between adolescents with ID and mental age-matched children. The results are discussed in terms of scientific and practical implications.